Local Identities : Landscape and Community in the Late Prehistoric Meuse-Demer-Scheldt Region. - Gerritsen, Fokke (Amsterdam Archaeological Studies, 9., 2003)
A study of the archaeologies of landscape and community in the Northwest European Plain.